Sistem Mafia Aplikasi Online Grab di Era Digitalisasi - Gilang Rizky Sampytho; Tutik Sulistyowati; Muhammad Hayat (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
The development of technology will be followed by the development of crime, one of which is the Grab online application mafia in the form of a fictional restaurant. Humans become objects so it must also be analyzed that the mafia experiences control by technology, it is an important subject when analyzing using the Herbert Mercuse theory. digitization. The research method used is qualitative, with a descriptive type of research. Descriptive is a type of qualitative research that describes problems that exist in society. The technique of determining the subject using purposive sampling. The analysis in this study uses Herbert Marcuse's theory of one dimension man and technological rationality. The findings of this study are the existence of a fictional restaurant by applying the mafia work system to take Grab promos with a crime system in the digitalization world. A fictional restaurant is a crime because stealing a Grab promo that is not carried out based on the system recommended by Grab. In fact, a fictitious order can be a profitable business between 3 parties. A number of drivers admit that the practice of fictitious orders is often deliberately carried out by the restaurant. According to them, Grab is not disadvantaged because the restaurant still does not pay taxes and sales traffic is high. Suggestions for the next writer related to this research are to focus on Grab bike drivers who often receive fictitious orders both in terms of receiving passenger orders, express and food delivery.